A high glow-wire halogen-free flame-retardant reinforced PA6 material and preparation method thereof

Through the use of modified combustion -free flame retardant and flame retardant coordinating agent in the reinforced PA6 material in the halogen -free flame retardant glass fiber, it solves the problem of insufficient burning temperature of the material. Performance and mechanical performance.

CN118772629BActive Publication Date: 2025-01-24CHANGZHOU WEICAI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411028789.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-01-24
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing halogen-free flame-retardant glass fiber reinforced PA6 material has a low ignition temperature, which cannot meet the requirements of electronic and electrical appliances for high glow wire temperature.

Method used

The cross -linking reaction system of ammonia propyl polybhenyl silicane and zinc phosphate was used to modify the halogen -free flame retardant, and combined with phosphate dilate as a flame retardant collaborative agent to optimize the proportion and processing of each component Process, improve the flame retardant performance and mechanical properties of materials.

Benefits of technology

The glow wire ignition temperature of the material is significantly increased, reaching 850°C, while maintaining good mechanical properties and processing properties, meeting the demand for high glow wire materials in electronic appliances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004969340700000091
    Figure BDA0004969340700000091
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and relates to a high glow-wire halogen-free flame-retardant reinforced PA6 material and a preparation method thereof. The material comprises the following components, calculated by weight: 40 to 55 parts of PA6 resin; 20 to 35 parts of glass fiber composite filler; 15 to 20 parts of modified halogen-free flame retardant; 2 to 3 parts of flame retardant synergist; 0.3 to 0.5 parts of antioxidant; 0.3 to 0.5 parts of lubricant; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate. A stable covalent cross-linking structure can be formed at high temperature, thereby improving the flame retardant performance and thermal stability of the material. On this basis, by adding diphenyl phosphate as a flame retardant synergist, the stability and aging resistance of the material in a high temperature environment can be effectively improved, which meets the requirements of the glow-wire material for a high temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a high glow-wire halogen-free flame-retardant reinforced PA6 material and a preparation method thereof. Background Art

[0002] Polyamide 6, or polycaprolactam (PA6), is one of the most widely used engineering plastics in the market. It has excellent mechanical properties, solvent and oil resistance, wear resistance, self-lubricating properties, and high heat resistance. Especially after being reinforced with glass fiber, its mechanical strength is significantly improved, while its heat resistance and dimensional stability are also significantly improved. This makes glass fiber reinforced PA6 widely used in many industries such as rail transportation, machinery, medical treatment and construction, and is favored for its high strength, good processability and excellent product design freedom. However, due to the candle wick effect of glass fiber, glass fiber reinforced PA6 material is very easy to burn, the flame propagates quickly, and it is a flammable material.

[0003] In the electronics and electrical industry, the requirements for materials are not limited to strength and dimensional stability, but also include flame retardancy. Flame retardancy is particularly important for unattended electrical products. Traditional brominated flame retardants are increasingly restricted due to their dioxin problems. Halogen-free flame retardants are environmentally friendly because they do not produce dioxin problems during combustion and are gradually replacing traditional brominated flame retardants. Although halogen-free flame retardants have good electrical properties, the glow wire temperature of halogen-free flame retardant polyester materials is low. Compared with halogen-containing flame retardant polyester materials, the glow wire ignition temperature of halogen-free flame retardant polyester materials drops from 850°C to 750°C or even lower, which cannot meet the high glow wire temperature requirements of electronic appliances for materials. At present, the general glass fiber reinforced halogen-free flame retardant PA6 glow wire (GWIT) on the market is not higher than 775 degrees. With the modular centralization of unattended electrical components, more electrical components will be gathered in a smaller space, and the local temperature will become higher. This use environment puts higher requirements on the glow wire of halogen-free flame retardant glass fiber reinforced PA6 materials. Therefore, how to improve the flame retardant properties while maintaining the mechanical strength of the material has become an important focus of current research.

[0004] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0005] The first object of the present invention is to provide a high glow-wire halogen-free flame-retardant reinforced PA6 material, which improves the flame retardant properties and the GWIT of the material while maintaining the mechanical strength of the material.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, comprises the following components:

[0008] PA6 resin: 40-55 parts;

[0009] Glass fiber composite filler: 20-35 parts;

[0010] Modified halogen-free flame retardant: 15-20 parts;

[0011] Flame retardant synergist: 2-3 parts;

[0012] Antioxidant: 0.3-0.5 parts;

[0013] Lubricant: 0.3-0.5 parts;

[0014] The modified halogen-free flame retardant is prepared by the cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein isocyanate is used as a cross-linking agent. Zinc phosphate is a highly polar inorganic compound, and aminopropyl polydiphenylsiloxane itself contains highly polar aminopropyl and non-polar diphenylsiloxane segments. In the absence of a cross-linking agent, complexation or physical mixing occurs between zinc phosphate and aminopropyl polydiphenylsiloxane, but this reaction is generally weak and insufficient to form a stable cross-linked network. After cross-linking with isocyanate, the benzene ring structure in isocyanate can not only interact with the phenyl in aminopropyl polydiphenylsiloxane, enhance the attraction between molecules, but also form coordination bonds with metal ions on the surface of zinc phosphate, and improve the interfacial bonding force of the material. Improving the compatibility between the organic-inorganic interface helps to form a uniform material structure and improve the overall performance of the material.

[0015] Furthermore, the preparation method of the modified halogen-free flame retardant comprises the following steps:

[0016] S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene under stirring to mix evenly, and then add isocyanate to ensure uniform dispersion; specifically toluene diisocyanate;

[0017] Wherein, in step S01, the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10-15:10-20:5-10:100-200. In the present invention, toluene diisocyanate is used as a cross-linking agent to connect aminopropyl polydiphenylsiloxane and zinc phosphate to form a stable cross-linked network, which can significantly enhance the mechanical properties and thermal stability of the material, thereby improving the flame retardant properties of the material. Isocyanate (-NCO) can react with amino (-NH2) or hydroxyl (-OH) in aminopropyl polydiphenylsiloxane to form urea (-NH-CO-NH-) and carbamate (-NH-CO-O-) structures, and can also react with hydroxyl (-OH) on the surface of zinc phosphate to form amino (-NH2) to continue to react with isocyanate (-NCO). The present invention uses isocyanate as a cross-linking agent to participate in the cross-linking of zinc phosphate and aminopropyl polydiphenylsiloxane for preparing a modified halogen-free flame retardant. Different from the conventional use of isocyanate in preparing polyurethane, the more complex and stable cross-linking network formed by the present invention can improve the heat resistance, flame retardancy and mechanical properties of the modified halogen-free flame retardant.

[0018] In the cross-linked structure after the reaction of the present invention, the Si-O-Si main chain structure of the polysiloxane and the aromatic ring structure in the diphenyl group have excellent thermal stability, can maintain their structural integrity under high temperature environment, and are not easy to decompose, thereby effectively improving the overall strength and thermal stability of the material. The high glow-wire halogen-free flame-retardant reinforced PA6 material is not easy to soften and melt under high temperature conditions, thereby reducing the dripping phenomenon. In addition, the polysiloxane can form silicon oxide (SiO2) with a high melting point, which can effectively cover the surface of the material to play a role in heat insulation and flame retardancy. The requirements for high glow-wire are particularly important. The aromatic hydrocarbons and soot particles generated by the decomposition of diphenyl during the combustion process can form a protective carbon layer on the surface of the material, blocking the transfer of oxygen and heat, and playing a flame retardant role. During the combustion process, the polysiloxane can further promote the formation of the carbon layer. The two work together to form a denser carbon layer during the combustion process, effectively blocking the transfer of flames and heat. Working together with the generated SiO2 layer, it can effectively reflect and absorb the heat generated during the combustion process, reduce the surface temperature of the material, and inhibit the continuation of combustion. In addition, the carbon dioxide and water generated during the combustion of xylene also have a dilution and cooling effect, further inhibiting the spread of flames, so that the modified halogen-free flame retardant can significantly improve the flame retardant properties of the material.

[0019] S02: Keep stirring and heat the mixture in S01 to 80-100°C for 1-3 hours. Observe the progress of the reaction and confirm the extent of the cross-linking reaction by sampling and analysis.

[0020] S03: After the reaction is completed, the mixture is cooled to room temperature, filtered to remove unreacted solids and impurities, and the toluene solvent is evaporated using a rotary evaporator, and then placed in a vacuum drying oven for further drying to obtain a modified halogen-free flame retardant.

[0021] Preferably, the mass ratio of aminopropyl polydiphenylsiloxane to PA6 resin is 1:4.5-5.5, and the further preferred mass ratio is 1:4.8-5.2. A further preferred mass ratio is 1:5. The present invention adjusts the content of urea groups and polysiloxane in the PA6 material by controlling the mass ratio of aminopropyl polydiphenylsiloxane to PA6 resin. The urea group itself does not directly act as a flame retardant. An appropriate amount of urea groups can form a dense carbon layer, which effectively blocks the entry of oxygen and the conduction of heat during the combustion process, thereby improving the flame retardant properties of the material. However, too many urea groups will increase the brittleness of the material, making the material more likely to break under impact loads, thereby reducing the impact strength of the material. Polysiloxane can ensure that a sufficiently thick and dense carbon layer is formed during combustion, while absorbing a large amount of heat and releasing free radical inhibitors, significantly improving the flame retardant properties of PA6. Under the premise of modifying the dosage of the halogen-free flame retardant, the present invention limits the mass ratio of aminopropyl polydiphenylsiloxane to PA6, so that the distribution of urea groups and the density of the formed carbon layer can effectively improve the comprehensive performance of the material, so that PA6 has excellent flame retardant properties and mechanical properties while maintaining good processing performance.

[0022] Preferably, the isocyanate is toluene diisocyanate, and multiple highly reactive isocyanate groups participate in the reaction to increase the crosslinking density of the entire system, thereby significantly improving the mechanical properties and thermal stability of the material.

[0023] Furthermore, the flame retardant synergist is diphenyl phosphate. The polar group of diphenyl phosphate can interact with the amide group in PA6 to enhance the interface bonding force. It forms a synergistic effect with the modified halogen-free flame retardant, which can improve the dispersibility of the modified halogen-free flame retardant in the PA6 matrix and effectively reduce the agglomeration of the flame retardant, thereby improving the mechanical properties and flame retardant properties of the composite material.

[0024] The present invention adopts diphenyl phosphate as a flame retardant synergist, wherein diphenyl phosphate decomposes at high temperature to generate phosphoric acid, and cooperates with zinc phosphate to form a more stable phosphate structure, which can effectively catalyze PA6 into carbon, form a stable carbon layer, play a role in heat insulation and oxygen isolation, thereby effectively preventing combustion, and the modified halogen-free flame retardant decomposes at high temperature to generate zinc oxide and release non-combustible water vapor, and zinc oxide is catalyzed into carbon, and non-combustible water vapor dilutes the combustible gas in the combustion area, and can reduce the combustion rate while providing additional thermal stability and physical barriers, thereby promoting PA6 to form a stable carbon layer at high temperature. The presence of urea and carbamate groups can enhance the thermal stability of the material, so that it can still maintain structural integrity at high temperatures, thereby slowing down the speed of flame spread. The two are used in coordination, which can significantly improve the carbonization efficiency of PA6, effectively prevent heat and oxygen from entering the interior of the material, thereby enhancing flame retardant properties.

[0025] The relative viscosity of PA6 resin is 2.8±1dL / g. Ensure the fluidity and molding performance of the material during processing, while maintaining excellent mechanical properties and heat resistance. PA6 resin can be purchased from the market. If the viscosity is too low, the PA6 material obtained will be too brittle. If the viscosity is too high, the preparation process will be unfavorable for the effective dispersion of the flame retardant. The relative viscosity of the PA6 resin of the present invention is controlled between 2.8±0.1, which can not only ensure that the filler is fully dispersed, but also the obtained high glow-wire halogen-free flame-retardant reinforced PA6 material has a certain toughness, meeting the technical requirements of the electronic and electrical industry.

[0026] Furthermore, the glass fiber composite filler is a compound made of alkali-free glass fiber and nano-scale filler powder in a mass ratio of 1:0.1 to 0.5. Alkali-free glass fiber has high strength and high modulus, and can effectively improve the tensile strength, bending strength and impact strength of PA6 resin. The composite material can withstand higher mechanical stress. Nano-scale filler powder has a high specific surface area and can be evenly filled in the tiny gaps of the PA6 matrix, which plays a role in refining the grains and improving the mechanical properties and thermal stability of the material. At the same time, the interface interaction between the resin and the fiber can be further improved by pre-mixing with alkali-free glass fiber. The present invention compounds alkali-free glass fiber and nano-scale filler powder in a mass ratio of 1:0.1 to 0.5, which can achieve a synergistic effect of the two, not only exerting the reinforcing effect of glass fiber, but also utilizing the refinement and reinforcing effect of nano-fillers to optimize the comprehensive performance of the composite material. At the same time, it effectively reduces the thermal expansion coefficient of the composite material, enhances its thermal stability, and reduces thermal deformation and thermal cracking.

[0027] Furthermore, the diameter of the alkali-free glass fiber is 10-14um, the length is 3.0-4.5mm, and the surface of the alkali-free glass fiber is modified by a silane coupling agent. The silane coupling agent is γ-aminopropyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane. γ-aminopropyltriethoxysilane is preferred. The silane coupling agent can improve the thermal stability of the glass fiber, so that it maintains structural integrity and performance stability under high temperature conditions.

[0028] Furthermore, the nano-scale filler powder includes one or more of aluminum hydroxide and silicon dioxide, with a particle size of 10 to 200 nm. The extremely small particle size and high surface area of ​​the nano-scale filler powder are conducive to uniform dispersion in the resin matrix, and can effectively transfer stress, thereby improving the tensile strength and impact strength of the material. Aluminum hydroxide and silicon dioxide can release water vapor at high temperatures. This release process absorbs a large amount of heat, thereby reducing the surface temperature of the material and slowing down or preventing the spread of flames. At the same time, they themselves have a high specific surface area and structural complexity. They can form a physical isolation layer in the polymer matrix to hinder the spread of flames and fuel gases, thereby slowing down the spread of flames. The above components are mixed with alkali-free glass fibers in one or more mixed ways to prepare glass fiber composite fillers. Due to the fine particles of the nano-scale filler powder, it can fill the microscopic cracks and gaps on the surface of the alkali-free glass fibers to form a uniform physical barrier to prevent direct contact and shear between the fibers and the resin, thereby enhancing the mechanical properties and durability of the composite material.

[0029] Furthermore, the antioxidant includes a mixture of a phosphite antioxidant and a hindered phenol antioxidant in a mass ratio of 1:1. Preferably, it is bis(2,4-di-tert-butylphenyl)pentaerythritol bisphosphite and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine. N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine is a hindered phenol compound, which can effectively terminate the bond breaking and decomposition of PA6 as a chain-terminating antioxidant; while bis(2,4-di-tert-butylphenyl)pentaerythritol bisphosphite is a protective antioxidant, which can effectively reduce the quinone structure to alcohol and reduce the activity of chain free radical reaction. The synergistic effect of the two can significantly reduce the decomposition of PA6 and improve the stability of the material.

[0030] Furthermore, the lubricant is at least one of calcium stearate, silicone, and PETS. The lubricant can reduce the friction between PA6 resin particles in the extruder, improve the fluidity of the material, reduce the adhesion between the resin and the mold surface, and help to obtain better molding performance and surface quality.

[0031] The second object of the present invention is to provide a method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material, which has simple steps, convenient operation and control, stable quality, high production efficiency, low production cost, and can be mass-produced industrially.

[0032] The above technical objectives of the present invention are achieved through the following technical solutions:

[0033] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0034] S1: Weigh each component according to its mass fraction;

[0035] S2: Dry the PA6 resin, alkali-free glass fiber and nano-scale filler powder; specifically, bake the PA6 resin at a temperature of 80℃ to 120℃ for 4 to 8 hours to dry it; to improve the processing stability and fluidity of the material, making it easier to form a uniform product during injection molding, extrusion and other processing processes, and reduce the changes and instability of the material during processing. Pre-dry the alkali-free glass fiber modified with silane coupling agent to remove surface moisture to avoid moisture and agglomeration when the nano-scale filler powder is attached. Ultrasonic dispersion treatment is performed on the nano-scale filler powder to break up the powder agglomerates to ensure that it is evenly dispersed, and then dried to remove moisture to prevent moisture absorption and agglomeration during the compounding process.

[0036] S3: premix the alkali-free glass fiber and the nano-grade filler powder to obtain a glass fiber composite filler; specifically, use a high-speed mixer to mix, and high-speed stirring can make the nano-grade filler powder evenly adhere to the surface of the glass fiber to form a glass fiber composite filler. The mixing time should be controlled within 15-30 minutes to ensure uniform distribution.

[0037] S4: Put PA6 resin, antioxidant and lubricant into a high-speed mixer and mix them thoroughly to obtain a premix; then gradually add the modified halogen-free flame retardant and flame retardant synergist in sequence and stir and mix them. After mixing evenly, they are conveyed to a twin-screw extruder through a feeding device, and the glass fiber composite filler is added from the side feeding port of the extruder; this can ensure that the ratio range of the length and diameter of the glass fiber composite filler is maximized, thereby improving the fiber reinforcement effect.

[0038] S5: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0039] Furthermore, the temperature parameters of each section of the twin-screw extruder are set as follows:

[0040] Zone 1 is 30-70℃, Zone 2 is 200-220℃, Zone 3 is 220-240℃, Zone 4 is 220-240℃, Zone 5 is 210-230℃, Zone 6 is 210-230℃, Zone 7 is 210-230℃, Zone 8 is 220-240℃, Zone 9 is 220-240℃, and the die head temperature is 220-240℃. The temperature in Zone 1 only plays a conveying role to prevent the material from melting too early, resulting in poor feeding and bridging of the material, so the temperature is relatively low; the temperature in Zones 2, 3, and 4 is relatively high, mainly for melting the material, the temperature in Zones 5, 6, and 7 is relatively low to prevent the degradation of the flame retardant, and the temperature in Zones 8 and 9 is relatively high, mainly because the higher temperature can reduce the viscosity of the plastic melt, facilitate vacuuming, and remove small molecules and moisture, making the PA6 flame retardant material have excellent performance.

[0041] The main engine speed of the twin-screw extruder is 200-400r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 5-10min. The present invention controls the temperature of the reaction zone between 220-240°C, and at the same time controls the aspect ratio of the twin-screw extruder to 36:1, and the high speed makes the flame retardant evenly dispersed in the PA6 matrix, thereby improving the dispersion of the flame retardant.

[0042] In summary, the present invention has the following beneficial effects:

[0043] (1) The present invention adopts aminopropyl polydiphenylsiloxane and zinc phosphate cross-linking reaction to prepare a modified halogen-free flame retardant, which can form a stable covalent cross-linking structure at high temperature, thereby improving the flame retardant properties and thermal stability of the material. The cross-linking reaction helps to improve the mechanical properties and durability of the material, so that it can better maintain its structural integrity during the flame retardant process. On this basis, by adding diphenyl phosphate as a flame retardant synergist, it synergizes with the modified halogen-free flame retardant to further improve the flame retardant properties of the material, reduce the amount of smoke released, and improve the flame propagation characteristics of the material. It can effectively improve the stability and aging resistance of the material in a high temperature environment, which meets the requirements of the glow wire material for a high temperature environment.

[0044] (2) The present invention can effectively enhance the mechanical strength and rigidity of the material by controlling the composite ratio and processing technology of the alkali-free glass fiber and the nano-scale filler, while reducing the weight of the material and improving its structural performance and wear resistance. Nano-scale filler powder has high surface energy and chemical reaction activity, and can effectively wrap the surface of the alkali-free glass fiber through physical adsorption. Since the nano-scale filler powder has fine particles, it can fill the microscopic cracks and gaps on the surface of the alkali-free glass fiber to form a uniform physical barrier. During the mixing process with the PA6 resin, the interfacial interaction between the resin and the fiber can be further improved. The bonding strength between the resin and the fiber is enhanced, thereby improving the mechanical properties and durability of the composite material.

[0045] (3) The present invention reasonably selects and optimizes the ratio of each component and the processing technology, so that the flame retardant properties, mechanical properties, thermal stability and processing properties of the glow-wire halogen-free flame retardant reinforced PA6 material are significantly improved, meeting the application requirements in high temperature environments and performing well in terms of environmental protection and sustainability. DETAILED DESCRIPTION

[0046] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a high glow-wire halogen-free flame-retardant reinforced PA6 material and a preparation method thereof proposed in accordance with the present invention, its specific implementation method, characteristics and effects are described in detail as follows.

[0047] Sources of materials in the specific implementation mode:

[0048] PA6 resin: B280A (viscosity = 2.8), Weiming Petrochemical Co., Ltd.;

[0049] Alkali-free glass fiber: 560A (diameter 10-14um, length 3.0-4.5mm), Jushi Group;

[0050] Nano-scale filler powder: aluminum hydroxide, silicon dioxide, Merck;

[0051] Modified halogen-free flame retardant: zinc phosphate, Changzhou Deshuo Chemical; aminopropyl polydiphenylsiloxane, toluene diisocyanate, methyl polysiloxane: Sinopharm Group;

[0052] Flame retardant synergist: diphenyl phosphate, Hubei Chushengwei Chemical Co., Ltd.;

[0053] Antioxidant: Antioxidant 1098, Tianjin Lianlong Materials Co., Ltd.; Antioxidant 626, Tianjin Lianlong Materials Co., Ltd.;

[0054] Lubricant: calcium stearate, Shanghai Myrel Chemical Technology Co., Ltd.; PRTS, Lonza, USA; silicone powder, Xingbeida Chemical Materials Co., Ltd.;

[0055] Example 1

[0056] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; aluminum hydroxide: 10 parts; modified halogen-free flame retardant: 18 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The preparation method of the modified halogen-free flame retardant includes the following steps:

[0057] S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene while stirring to mix evenly, and then add toluene diisocyanate to ensure uniform dispersion; the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:17:5:200.

[0058] S02: Keep stirring and heat the mixture in S01 to 90°C for 1.5h;

[0059] S03: After the reaction is completed, the mixture is cooled to room temperature, filtered to remove unreacted solids and impurities, and the toluene solvent is evaporated using a rotary evaporator, and then placed in a vacuum drying oven for further drying to obtain a modified halogen-free flame retardant.

[0060] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0061] S1: Weigh each component according to its mass fraction;

[0062] S2: baking PA6 resin, alkali-free glass fiber and aluminum hydroxide at 100°C until dry;

[0063] S3: premixing the alkali-free glass fiber and aluminum hydroxide for 20 minutes using a high-speed mixer to obtain a glass fiber composite filler;

[0064] S4: PA6 resin, antioxidant 1098, antioxidant 626 and calcium stearate are put into a high-speed mixer and fully mixed to obtain a premix; then the modified halogen-free flame retardant and diphenyl phosphate are gradually added in sequence and stirred and mixed. After mixing evenly, the mixture is conveyed to a twin-screw extruder through a feeding device, and the glass fiber composite filler is added from the side feeding port of the extruder;

[0065] S5: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0066] Further, the temperature parameters of each section of the twin-screw extruder are set as follows: 50°C in zone 1, 220°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 230°C in zone 8, 240°C in zone 9, and the die head temperature is 240°C. The main engine speed of the twin-screw extruder is 300r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 8min.

[0067] Example 2

[0068] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; silicon dioxide: 10 parts; modified halogen-free flame retardant: 19 parts; diphenyl phosphate: 3 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; PETS: 0.4 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The preparation method of the modified halogen-free flame retardant includes the following steps:

[0069] S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene while stirring to mix evenly, and then add toluene diisocyanate to ensure uniform dispersion; the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:16:5:200.

[0070] S02: Keep stirring and heat the mixture in S01 to 90°C for 1.5h;

[0071] S03: After the reaction is completed, the mixture is cooled to room temperature, filtered to remove unreacted solids and impurities, and the toluene solvent is evaporated using a rotary evaporator, and then placed in a vacuum drying oven for further drying to obtain a modified halogen-free flame retardant.

[0072] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0073] S1: Weigh each component according to its mass fraction;

[0074] S2: baking PA6 resin, alkali-free glass fiber and silica at 100°C until dry;

[0075] S3: premixing the alkali-free glass fiber and silica for 25 minutes using a high-speed mixer to obtain a glass fiber composite filler;

[0076] S4: PA6 resin, antioxidant 1098, antioxidant 626 and PETS are put into a high-speed mixer and fully mixed to obtain a premix; then the modified halogen-free flame retardant and diphenyl phosphate are gradually added in sequence and stirred and mixed. After mixing evenly, the mixture is conveyed to a twin-screw extruder through a feeding device, and the glass fiber composite filler is added from the side feeding port of the extruder;

[0077] S5: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0078] Further, the temperature parameters of each section of the twin-screw extruder are set as follows: 50°C in zone 1, 220°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 230°C in zone 8, 240°C in zone 9, and the die head temperature is 240°C. The main engine speed of the twin-screw extruder is 400r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 8min.

[0079] Example 3

[0080] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 55 parts; alkali-free glass fiber: 30 parts; silicon dioxide: 5 parts; modified halogen-free flame retardant: 20 parts; diphenyl phosphate: 3 parts; antioxidant 1098: 0.25 parts; antioxidant 626: 0.25 parts; silicone powder: 0.5 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The preparation method of the modified halogen-free flame retardant includes the following steps:

[0081] S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene while stirring to mix evenly, and then add toluene diisocyanate to ensure uniform dispersion; the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:18:6:200.

[0082] S02: Keep stirring and heat the mixture in S01 to 90°C for 1.5h;

[0083] S03: After the reaction is completed, the mixture is cooled to room temperature, filtered to remove unreacted solids and impurities, and the toluene solvent is evaporated using a rotary evaporator, and then placed in a vacuum drying oven for further drying to obtain a modified halogen-free flame retardant.

[0084] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0085] S1: Weigh each component according to its mass fraction;

[0086] S2: baking PA6 resin, alkali-free glass fiber and silica at 100°C until dry;

[0087] S3: premixing the alkali-free glass fiber and silica for 20 minutes using a high-speed mixer to obtain a glass fiber composite filler;

[0088] S4: PA6 resin, antioxidant 1098, antioxidant 626 and silicone powder are put into a high-speed mixer and fully mixed to obtain a premix; then modified halogen-free flame retardant and diphenyl phosphate are gradually added in sequence and stirred and mixed. After mixing evenly, the mixture is conveyed to a twin-screw extruder through a feeding device, and the glass fiber composite filler is added from the side feeding port of the extruder;

[0089] S5: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0090] Further, the temperature parameters of each section of the twin-screw extruder are set as follows: 50°C in zone 1, 220°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 230°C in zone 8, 240°C in zone 9, and the die head temperature is 240°C. The main engine speed of the twin-screw extruder is 250r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 10min.

[0091] Example 4

[0092] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 40 parts; alkali-free glass fiber: 15 parts; aluminum hydroxide: 5 parts; modified halogen-free flame retardant: 18 parts; diphenyl phosphate: 3 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.3 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The preparation method of the modified halogen-free flame retardant includes the following steps:

[0093] S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene while stirring to mix evenly, and then add toluene diisocyanate to ensure uniform dispersion; the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 15:20:10:200.

[0094] S02: Keep stirring and heat the mixture in S01 to 90°C for 1.5h;

[0095] S03: After the reaction is completed, the mixture is cooled to room temperature, filtered to remove unreacted solids and impurities, and the toluene solvent is evaporated using a rotary evaporator, and then placed in a vacuum drying oven for further drying to obtain a modified halogen-free flame retardant.

[0096] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0097] S1: Weigh each component according to its mass fraction;

[0098] S2: baking PA6 resin, alkali-free glass fiber and aluminum hydroxide at 100°C until dry;

[0099] S3: premixing the alkali-free glass fiber and aluminum hydroxide for 20 minutes using a high-speed mixer to obtain a glass fiber composite filler;

[0100] S4: PA6 resin, antioxidant 1098, antioxidant 626 and calcium stearate are put into a high-speed mixer and fully mixed to obtain a premix; then the modified halogen-free flame retardant and diphenyl phosphate are gradually added in sequence and stirred and mixed. After mixing evenly, the mixture is conveyed to a twin-screw extruder through a feeding device, and the glass fiber composite filler is added from the side feeding port of the extruder;

[0101] S5: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0102] Further, the temperature parameters of each section of the twin-screw extruder are set as follows: 50°C in zone 1, 220°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 230°C in zone 8, 240°C in zone 9, and the die head temperature is 240°C. The main engine speed of the twin-screw extruder is 300r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 8min.

[0103] Example 5

[0104] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 45 parts; alkali-free glass fiber: 20 parts; aluminum hydroxide: 10 parts; modified halogen-free flame retardant: 20 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.15 parts; antioxidant 626: 0.15 parts; PETS: 0.3 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The preparation method of the modified halogen-free flame retardant includes the following steps:

[0105] S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene while stirring to mix evenly, and then add toluene diisocyanate to ensure uniform dispersion; the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:20:10:200.

[0106] S02: Keep stirring and heat the mixture in S01 to 90°C for 1.5h;

[0107] S03: After the reaction is completed, the mixture is cooled to room temperature, filtered to remove unreacted solids and impurities, and the toluene solvent is evaporated using a rotary evaporator, and then placed in a vacuum drying oven for further drying to obtain a modified halogen-free flame retardant.

[0108] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0109] S1: Weigh each component according to its mass fraction;

[0110] S2: baking PA6 resin, alkali-free glass fiber and aluminum hydroxide at 100°C until dry;

[0111] S3: premixing the alkali-free glass fiber and aluminum hydroxide for 20 minutes using a high-speed mixer to obtain a glass fiber composite filler;

[0112] S4: PA6 resin, antioxidant 1098, antioxidant 626 and PETS are put into a high-speed mixer and fully mixed to obtain a premix; then the modified halogen-free flame retardant and diphenyl phosphate are gradually added in sequence and stirred and mixed. After mixing evenly, the mixture is conveyed to a twin-screw extruder through a feeding device, and the glass fiber composite filler is added from the side feeding port of the extruder;

[0113] S5: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0114] Further, the temperature parameters of each section of the twin-screw extruder are set as follows: 50°C in zone 1, 220°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 230°C in zone 8, 240°C in zone 9, and the die head temperature is 240°C. The main engine speed of the twin-screw extruder is 300r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 8min.

[0115] Comparative Example 1 (Too many urea groups)

[0116] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; aluminum hydroxide: 10 parts; modified halogen-free flame retardant: 25 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:17:5:200. The rest is exactly the same as Example 1 and will not be repeated here.

[0117] Comparative Example 2 (too few urea groups)

[0118] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; aluminum hydroxide: 10 parts; modified halogen-free flame retardant: 12 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:17:5:200. The rest is exactly the same as Example 1 and will not be repeated here.

[0119] Comparative Example 3 (without adding nano filler powder)

[0120] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; modified halogen-free flame retardant: 12 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. The mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10:17:5:200. The preparation method of the modified halogen-free flame retardant is exactly the same as that of Example 1, and will not be repeated here.

[0121] A method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material comprises the following steps:

[0122] S1: Weigh each component according to its mass fraction;

[0123] S2: baking the PA6 resin and the alkali-free glass fiber at 100°C until dry;

[0124] S3: PA6 resin, antioxidant 1098, antioxidant 626 and calcium stearate are put into a high-speed mixer and fully mixed to obtain a premix; then the modified halogen-free flame retardant and diphenyl phosphate are gradually added in sequence and stirred and mixed. After mixing evenly, the mixture is conveyed to a twin-screw extruder through a feeding device, and the alkali-free glass fiber is added from the side feeding port of the extruder;

[0125] S4: After the mixture is melt-kneaded, it is granulated and dried to obtain a high glow-wire halogen-free flame-retardant reinforced PA6 material.

[0126] Further, the temperature parameters of each section of the twin-screw extruder are set as follows: 50°C in zone 1, 220°C in zone 2, 230°C in zone 3, 230°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 230°C in zone 8, 240°C in zone 9, and the die head temperature is 240°C. The main engine speed of the twin-screw extruder is 300r / min, the side feed speed of the twin-screw extruder is 150r / min, and the time is 8min.

[0127] Comparative Example 4 (using only zinc phosphate)

[0128] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; aluminum hydroxide: 10 parts; zinc phosphate: 18 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the rest is exactly the same as in Example 1 and will not be repeated here.

[0129] Comparative Example 5 (Zinc phosphate and aminopropyl polydiphenylsiloxane are not cross-linked)

[0130] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; aluminum hydroxide: 10 parts; modified halogen-free flame retardant: 18 parts; diphenyl phosphate: 2 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the modified halogen-free flame retardant is a mixture of aminopropyl polydiphenylsiloxane and zinc phosphate in a mass ratio of 10:17. In this comparative example, zinc phosphate and aminopropyl polydiphenylsiloxane are not cross-linked, and the rest is exactly the same as Example 1, which will not be repeated here.

[0131] Comparative Example 6 (without addition of diphenyl phosphate)

[0132] A high glow-wire halogen-free flame-retardant reinforced PA6 material, calculated by weight, includes the following components: PA6 resin: 50 parts; alkali-free glass fiber: 25 parts; aluminum hydroxide: 10 parts; modified halogen-free flame retardant: 18 parts; antioxidant 1098: 0.2 parts; antioxidant 626: 0.2 parts; calcium stearate: 0.5 parts; the modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein toluene diisocyanate is used as a cross-linking agent. In this comparative example, diphenyl phosphate is not added, and the rest is exactly the same as Example 1, which will not be repeated here.

[0133] Performance Testing

[0134] The high glow-wire halogen-free flame-retardant reinforced PA6 materials obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were dried in an oven at 100 to 120° C. for 4 hours and then injection molded into standard test strips. The mechanical properties of the standard test strips of the above embodiments were tested, the tensile strength was tested according to ISO527-2012, the simply supported beam notched impact strength was tested according to ISO179-2010, and the bending strength was tested according to ISO178-2019, wherein the GWIT performance was tested according to IEC60695, and the UL94 flame retardant test was tested according to the 1.6 mm strip test standard UL94-2018.

[0135] The test results are shown in Table 1:

[0136] Table 1. Test results of flame retardant reinforced material properties of Examples 1 to 5 and Comparative Examples 1 to 6

[0137]

[0138] As can be seen from the table, according to the present invention, a high glow-wire halogen-free flame-retardant reinforced PA6 material and a preparation method thereof not only achieves GWIT of 850°C and 1.6mm V-0 flame retardancy, but also has good mechanical properties, which can fully meet the requirements of electronic PA6 materials for high glow-wire, and is particularly suitable for outdoor unattended electronic equipment products.

[0139] Compared with Example 1, the mass ratio of aminopropyl polydiphenylsiloxane to PA6 resin in Comparative Example 1 is too large, and the resulting material is significantly inferior to Example 1 in terms of mechanical properties and flame retardancy. This is mainly because the increase in the amount of flame retardant increases the flame retardancy of the material while reducing the mechanical properties. Although urea groups can enhance the mechanical properties of the material, too many urea groups will increase the brittleness of the material, making the material more likely to break under impact loads, thereby reducing the impact strength of the material.

[0140] Compared with Example 1, in Comparative Example 2, the amount of modified halogen-free flame retardant is less, and the mass ratio of aminopropyl polydiphenylsiloxane to PA6 resin is too small, and the resulting material is significantly inferior to Example 1 in both mechanical properties and flame retardant properties. This is mainly because too few urea groups cannot provide sufficient structural support, resulting in insufficient tensile strength and bending strength of the material, affecting the performance of the material. And it is impossible to form a sufficiently dense carbon layer, causing the material to be easily oxidized and decomposed during the combustion process, thereby reducing the flame retardant properties of the material. And combined with Comparative Example 1, it can be explained that the addition of flame retardants will reduce the mechanical properties of the material. The present invention achieves a balance between the mechanical properties and flame retardant properties of the material, so that PA6 has excellent flame retardant properties and mechanical properties while maintaining good processing properties.

[0141] Compared with Example 1, Comparative Example 3 does not add nano-filler powder, that is, glass fiber reinforcement is directly used. The mechanical properties are lower than those of Comparative Example 1, indicating that the extremely small particle size and high surface area of ​​the nano-scale filler powder are conducive to uniform dispersion in the resin matrix and can effectively transfer stress, thereby improving the tensile strength and impact strength of the material.

[0142] In Comparative Example 4, compared with Example 1, only unmodified zinc phosphate is used, and the corresponding components of zinc phosphate are increased, but its GWIT is reduced by 25°C, the flame retardant grade of UL94 / 1.6mm is V-1, the mechanical properties are also reduced, and the glow-wire ignition time and flame self-extinguishing time are poor, indicating that the more stable covalent cross-linked structure formed by the present invention can effectively fix aminopropyl polydiphenylsiloxane on the surface of zinc phosphate, thereby improving the mechanical strength and thermal stability of the material.

[0143] In Comparative Example 5, relative to Example 1, zinc phosphate and aminopropyl polydiphenylsiloxane are not cross-linked, and various properties are reduced, indicating that the present invention realizes the cross-linking reaction of zinc phosphate and aminopropyl polydiphenylsiloxane by using isocyanate as a cross-linking agent, and the presence of urea group and carbamate group can prompt the material to form a more stable and dense carbon layer during the combustion process, thereby improving the flame retardant performance.

[0144] Comparative Example 6, compared with Example 1, does not use a flame retardant synergist, and all properties are reduced, indicating that the use of diphenyl phosphate as a flame retardant synergist in combination with the modified halogen-free flame retardant significantly improves the mechanical properties, flame retardant properties and thermal stability of the PA6 composite material. This is mainly because diphenyl phosphate improves the dispersibility of the flame retardant and the interface compatibility with the PA6 matrix, thereby making the material perform better during heating and combustion.

[0145] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been presented as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A high glow-wire halogen-free flame-retardant reinforced PA6 material, characterized in that: Calculated by weight, it includes the following components: PA6 resin: 40-55 parts; Glass fiber composite filler: 20-35 parts; Modified halogen-free flame retardant: 15~20 parts; Flame retardant synergist: 2~3 parts; Antioxidant: 0.3-0.5 parts; Lubricant: 0.3-0.5 parts; The modified halogen-free flame retardant is prepared by cross-linking reaction of aminopropyl polydiphenylsiloxane and zinc phosphate, wherein isocyanate is used as a cross-linking agent; The mass ratio of aminopropyl polydiphenylsiloxane to PA6 resin is 1:4.5-5.5, the isocyanate is toluene diisocyanate, the flame retardant synergist is diphenyl phosphate, and the glass fiber composite filler is a compound prepared by alkali-free glass fiber and nano-scale filler powder in a mass ratio of 1:0.1-0.5, and the nano-scale filler powder includes one or more of aluminum hydroxide and silicon dioxide.

2. The high glow-wire halogen-free flame-retardant reinforced PA6 material according to claim 1, characterized in that: The preparation method of the modified halogen-free flame retardant comprises the following steps: S01: Grind zinc phosphate to 1-10 μm, slowly and gradually add zinc phosphate and aminopropyl polydiphenylsiloxane into toluene while stirring, and then add isocyanate to ensure uniform dispersion; S02: Keep stirring and heat the mixture in S01 to 80-100°C for 1-3 hours; S03: After the reaction is completed, the mixture is cooled to room temperature, filtered, evaporated to remove insoluble matter and toluene, and then dried to obtain a modified halogen-free flame retardant.

3. The high glow-wire halogen-free flame-retardant reinforced PA6 material according to claim 2, characterized in that: In step S01, the mass ratio of zinc phosphate, aminopropyl polydiphenylsiloxane, toluene diisocyanate and toluene is 10-15:10-20:5-10:100-200.

4. The high glow-wire halogen-free flame-retardant reinforced PA6 material according to claim 1, characterized in that: The diameter of the alkali-free glass fiber is 10-14 μm, the length is 3.0-4.5 mm, and the surface of the alkali-free glass fiber is modified by a silane coupling agent.

5. The high glow-wire halogen-free flame-retardant reinforced PA6 material according to claim 1, characterized in that: The lubricant is at least one of calcium stearate, silicone and PETS.

6. The method for preparing a high glow-wire halogen-free flame-retardant reinforced PA6 material according to any one of claims 1 to 5, characterized in that: The steps are as follows: S1: Weigh each component according to its mass fraction; S2: Drying the PA6 resin, alkali-free glass fiber and nano-scale filler powder; S3: premixing the alkali-free glass fiber and the nano-scale filler powder to obtain a glass fiber composite filler; S4: Put PA6 resin, antioxidant and lubricant into a high-speed mixer and mix them thoroughly to obtain a premix; then add the modified halogen-free flame retardant and flame retardant synergist in sequence and continue to stir and mix. After mixing evenly, convey them to a twin-screw extruder through a feeding device, and add the glass fiber composite filler from the side feeding port of the extruder; S5: After the mixture is melt-kneaded, it is granulated and dried to obtain the high glow-wire halogen-free flame-retardant reinforced PA6 material.

Citation Information

Patent Citations

  • Drainage anti-fouling pipe with good weather resistance for water conservancy and hydropower construction

    CN106543678A

  • Antibacterial universal plastic material and preparation method thereof

    CN113248860A